POROSITAS, KUAT TEKAN DAN KUAT TARIK BELAH BETON DENGAN AGREGAT KASAR BATU PECAH PASCA DIBAKAR - Gede Sutapa, A.A. (Jurnal Ilmiah Teknik Sipil; Vol. 15, No. 1 Januari 2011)
Porosity can be defined as a ratio of pore volume (volume occupied by the fluid) to total volume of concrete. Porosity in concrete is important to be studied; especially for materials of seaside buildings and buildings attaching the ground. Salt water containing sulfate and chloride can press the pores of concrete so that concrete cracks into loose flakes and its strength reduces. An increase in porosity is thought to associate with a reduced strength of post-burnt concrete. Research was conducted to study the compressive strength, splitting tensile and porosity of post-burnt concrete using cylinders of 150 mm diameter and 300 mm high. Burning of samples was carried out after 28 days of age. The burning was started at an oven temperature of 34 º C until it reached a maximum temperature of ± 800 º C achieved at minute of 180 and then it held on for another 20 minutes, so that the burning process lasted for 200 minutes. The test results showed that the increase in porosity of concrete is proportional to the volume of concrete that had hot penetration with temperature 400-800 oC. The porosity of concrete increased by 20.695%, which resulted in the decrease of compressive strength and splitting tensile strength by 53.665% and 49.641% respectively.
Keywords: Porosity of concrete, hot penetration, compressive strength of concrete, splitting tensile strength of concrete, after burning.